2019
DOI: 10.3390/toxins11100559
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Characteristics of Antimicrobial α-Helical Peptides Found in Solitary Wasp Venoms and Their Interactions with Model Membranes

Abstract: Solitary wasps use their stinging venoms for paralyzing insect or spider prey and feeding them to their larvae. We have surveyed bioactive substances in solitary wasp venoms, and found antimicrobial peptides together with some other bioactive peptides. Eumenine mastoparan-AF (EMP-AF) was the first to be found from the venom of the solitary eumenine wasp Anterhynchium flavomarginatum micado, showing antimicrobial, histamine-releasing, and hemolytic activities, and adopting an α-helical secondary structure under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 96 publications
(217 reference statements)
1
34
0
Order By: Relevance
“…Neuro-VAL had a lower hydrophobic moment (0.17); this suggests that it probably interacts poorly with cell membranes. [24] To characterize the secondary structures of the peptides we recorded circular dichroism (CD) spectra. The spectra indicated that the peptides were unstructured in water, as expected for linear peptides.…”
Section: Synthesis and Structural Characterization Of Wasp-derived Pementioning
confidence: 99%
“…Neuro-VAL had a lower hydrophobic moment (0.17); this suggests that it probably interacts poorly with cell membranes. [24] To characterize the secondary structures of the peptides we recorded circular dichroism (CD) spectra. The spectra indicated that the peptides were unstructured in water, as expected for linear peptides.…”
Section: Synthesis and Structural Characterization Of Wasp-derived Pementioning
confidence: 99%
“…The antimicrobial property of V. orientalis venoms is mostly due to their peptides. Many authors detected the antimicrobial properties of different wasp venoms [22,25] . Isolated AMPs from the V. orientalis venom affected the tested bacterial ultrastructure (Figures 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of cationic, amphiphilic substances, including neuropeptides, hormones, venom peptides, and polyamines, exhibited activating properties on purified G proteins. They have a high proportion of hydrophobic and basic groups orienting in an amphipathic α‐helical structure in the presence of phospholipids (Figure 4C), and allowing them to penetrate the cell membrane [134,135] . Prominent members of this group are the wasp venom 14mer peptide mastoparan (H‐INLKALAALAKKIL‐NH 2 ) and the bee venom 26mer peptide melittin (H‐GIGAVLKVLTTGLPALISWIKRKRQQ‐NH 2 ).…”
Section: Modulators Targeting Gαi/s Interfacesmentioning
confidence: 99%